Cardiac Myosin Binding Protein-C Phosphorylation Modulates Myofilament Length-Dependent Activation - Mamidi, Ranganath; Gresham, Kenneth S.; Verma, Sujeet; Stelzer, Julian E. (Frontiers in Physiology, 2016)
Cardiac myosin binding protein-C (cMyBP-C) phosphorylation is an important regulator of contractile function, however, its contributions to length-dependent (SL) changes in cross-bridge (XB) kinetics is unknown. Therefore, we performed mechanical experiments to quantify contractile function in detergent-skinned ventricular preparations isolated from wild-type (WT) hearts, and hearts expressing non-phosphorylatable cMyBP-C (Ser to Ala substitutions at residues Ser273, Ser282, and Ser302 (i.e., 3SA)), at SL 1.9µm or 2.1µm, prior and following protein kinase A (PKA) treatment. Steady-state force generation measurements revealed a blunting in the length-dependent increase in myofilament Ca2+-sensitivity of force generation (pCa50) following an increase in SL in 3SA skinned myocardium compared to WT skinned myocardium. Dynamic XB behavior was assessed at submaximal Ca2+-activations by imposing an acute rapid stretch of 2% of initial muscle length, and measuring both the magnitudes and rates of resultant phases of force decay due to strain-induced XB detachment and delayed force rise due to recruitment of additional XBs with increased SL (i.e., stretch activation). The magnitude (P2) and rate of XB detachment (krel) following stretch was significantly reduced in 3SA skinned myocardium compared to WT skinned myocardium at short and long SL, and prior to and following PKA treatment. Furthermore, the length-dependent acceleration of krel due to decreased SL that was observed in WT skinned myocardium was abolished in 3SA skinned myocardium. PKA treatment accelerated the rate of XB recruitment (kdf) following stretch at both SL’s in WT but not in 3SA skinned myocardium. The amplitude of the enhancement in force generation above initial pre-stretch steady-state levels (P3) was not different between WT and 3SA skinned myocardium at any condition measured. However, the magnitude of the entire delayed force phase which can dip below initial pre-stretch steady-state levels (Pdf) was significantly lower in 3SA skinned myocardium under all conditions, in part due to a reduced magnitude of XB detachment (P2) in 3SA skinned myocardium compared to WT skinned myocardium. These findings demonstrate that cMyBP-C phospho-ablation regulates SL- and PKA-mediated effects on XB kinetics in the myocardium, which would be expected to contribute to the regulation of the Frank-Starling mechanism.